Addition of Poa calliopsis (Poaceae: Pooideae: Poeae) to the flora of Eastern Himalaya, India - Saha, S.; Ghosh, J.; Midday, M.; Halder, A.K.; Mandal, M.; Maity, D. (Rheedea, 2024)
In India, Poa calliopsis Litv. ex Ovcz. was known only from two Western Himalayan states, Jammu & Kashmir and Himachal Pradesh. However, the present record of this species in Sikkim reveals its occurrence in the Indian Eastern Himalayan region. A detailed description, photo plate and illustration of the species along with notes on its habitat, phenology and distribution are presented here. Notes on the affinities of this species with allied taxa are also incorporated. An identification key to the species of Poa of Indian Eastern Himalaya is provided.